2018
DOI: 10.1007/s00360-018-1186-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular resistance to thrombosis in 13-lined ground squirrels

Abstract: Thirteen-lined ground squirrels (Ictidomys tridecemlineatus) enter hibernation as a survival strategy during extreme environmental conditions. Typical ground squirrel hibernation is characterized by prolonged periods of torpor with significantly reduced heart rate, blood pressure, and blood flow, interrupted every few weeks by brief interbout arousals (IBA) during which blood flow fluctuates dramatically. These physiological conditions should increase the risk of stasisinduced blood clots and myocardial ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…CK‐MB plays an important role in cellular energy metabolism, and therefore a decrease in CK‐MB was consistent with reduced energy requirements of the heart and muscle during hibernation (Abnous & Storey, 2007; Barrows et al, 2011). The finding that cTnI was significantly higher in 13‐lined ground squirrel plasma in the IBA group as compared with the LT group supported our findings (Bonis et al, 2019). Therefore, we assumed that the dynamic changes in cTnI seen over torpor‐arousal cycles indicated the adaptive response of the myocardium, in which the myocardial cells were able to repair themselves and gradually restore their normal function after repeated I/R injury.…”
Section: Discussionsupporting
confidence: 91%
“…CK‐MB plays an important role in cellular energy metabolism, and therefore a decrease in CK‐MB was consistent with reduced energy requirements of the heart and muscle during hibernation (Abnous & Storey, 2007; Barrows et al, 2011). The finding that cTnI was significantly higher in 13‐lined ground squirrel plasma in the IBA group as compared with the LT group supported our findings (Bonis et al, 2019). Therefore, we assumed that the dynamic changes in cTnI seen over torpor‐arousal cycles indicated the adaptive response of the myocardium, in which the myocardial cells were able to repair themselves and gradually restore their normal function after repeated I/R injury.…”
Section: Discussionsupporting
confidence: 91%
“…Upon fibrinolysis, fibrin in a clot is cleaved into fibrin degradation products, of which D-dimers can be detected in plasma and is commonly used in the diagnosis of venous or arterial thrombosis. In bears, hamsters, and ground squirrels no increases in D-dimers are seen during hibernation, consistent with low levels of clot formation and fibrinolysis (Iles et al, 2017;Bonis et al, 2019). The lack of D-dimers is consistent with suppression of secondary hemostasis and absence of actual clot fibrinolysis during torpor, while the hyperfibrinolytic state reflected by increased tPA and PAI-1 may be an added layer of protection in the event that a clot does form (Figure 7).…”
Section: Fibrinolysis Adaptations During Torpormentioning
confidence: 74%
“…An alternative to reducing clotting Frontiers in Physiology frontiersin.org factors would be to increase anticoagulants. Yet, the anticoagulant proteins antithrombin and protein C are not reduced in torpid hamsters and ground squirrels (Bonis et al, 2019). However, in hibernating bears antithrombin levels are reduced, but it is not known if this is due to decreased production of antithrombin or increased consumption (Welinder et al, 2016).…”
Section: Secondary Hemostasis Adaptations During Torpormentioning
confidence: 99%
“…Using brown bears ( Ursus arctos ), the researchers found that winter bear serum could reduce the protein turnover of myotubes, thereby maintain muscle mass and strength during hibernation, and it might be useful for developing new tools to fighting human muscle atrophy [30]. In 13-lined ground squirrels ( Ictidomys tridecemlineatus ) [31], thrombosis and myocardial ischemia do not occur during hibernation (during which non-hibernating animals are more likely to get thrombosis and myocardial ischemia). This phenomenon indicates that hibernating mammalian animals are natural cardiovascular disease research models.…”
Section: Discussionmentioning
confidence: 99%